Ball milling potassium ferrate activated biochar for efficient chromium and tetracycline decontamination: Insights into activation and adsorption mechanisms. (September 2022) - Qu, Jianhua; Wu, Zhihuan; Liu, Yang; Li, Ruolin; Wang, Di; Wang, Siqi; Wei, Shuqi; Zhang, Jingru; Tao, Yue; Jiang, Zhao; Zhang, Ying
Graphical abstract: Highlights: K2 FeO4 and ball milling were innovatively combined for decorating biochar. Synergistic effects of chemical activation and physical modification were explored. MBCBM700 had a higher uptake ability of Cr(VI)/TC (117.49/90.31 mg/g) than MBCBM500 . The abundant Fe 0 of MBCBM700 surface promoted Cr(VI) removal by reduction. MBCBM500/700 eliminated TC via hydrogen bonding force, pore filling and π-π stacking. Abstract: Herein, novel Fe-biochar composites (MBCBM500 and MBCBM700 ) were synthesized through K2 FeO4 co-pyrolysis and ball milling, and were used to eliminate Cr(VI)/TC from water. Characterization results revealed that higher temperature promoted formation of zero-valent iron and Fe3 C on MBCBM700 through carbothermal reduction between K2 FeO4 and biochar. The higher specific surface area and smaller particle size of MBCBM500/700 stemmed from the corrosive functions of K and the ball milling process. And the maximal uptake amount of MBCBM700 for Cr(VI)/TC was 117.49/90.31 mg/g, relatively higher than that of MBCBM500 (93.86/84.15 mg/g). Furthermore, ion exchange, pore filling, precipitation, complexation, reduction and electrostatic attraction were proved to facilitate the adsorption of Cr(VI), while hydrogen bonding force, pore filling, complexation and π-π stacking were the primary pathways to eliminate TC. This study provide a reasonable design of Fe-carbon materials for Cr(VI)/TC contained water remediation, which required neither extra modifiers nor complex preparation process.